2016
DOI: 10.1039/c6nj02367c
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory parameters of self-healing alginate hydrogel networks prepared via mussel-inspired dynamic chemistry

Abstract: Key parameters that influence the self-healing and water retention properties of hydrogels made of alginate–dopamine conjugates have been revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…The wide range of dopamine grafting is achieved by altering the molar ratios of alginate to dopamine. The UV–visible absorption spectroscopy at 280 nm of the alginate–dopamine polymer revealed a dopamine content of 26%, which is close to the dopamine content in Mfp‐3, and also is within the range of dopamine content reported in other dopamine conjugated alginate polymers …”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The wide range of dopamine grafting is achieved by altering the molar ratios of alginate to dopamine. The UV–visible absorption spectroscopy at 280 nm of the alginate–dopamine polymer revealed a dopamine content of 26%, which is close to the dopamine content in Mfp‐3, and also is within the range of dopamine content reported in other dopamine conjugated alginate polymers …”
Section: Resultssupporting
confidence: 79%
“…The dopamine content in mussel foot proteins (Mfps) varies from 10% to 15% in Mfp‐1, 2% to 4% in Mfp‐2, 25% in Mfp‐3, 5% in Mfp‐4, and 30% in Mfp‐5, whereas Mfp‐3 and Mfp‐5 are the proteins that contact the surface and help mussels adhere to wet surfaces . Some research groups reported that the dopamine contents incorporated into alginate ranged from 10% to 42% . The wide range of dopamine grafting is achieved by altering the molar ratios of alginate to dopamine.…”
Section: Resultsmentioning
confidence: 99%
“…[86][87][88][89][90][91] Mussel-inspired biomimetic polymers have been mainly prepared from polyesters, [88,89] polyamides, [92] polyacrylates, [93][94][95][96] polyethylene glycols, [16,[97][98][99] polyoxetanes, [87,91] polystyrenes [86,100] polypeptides, [101][102][103] and polysaccharides. [104,105] Ther esults defined ar ange for the optimal catechol content close to that observed in mfps,b ut with differences depending on the nature of the material used. However, despite this growing number of synthetic polymers mimicking adhesive proteins of mussels,the number of detailed and systematic studies aimed at elucidating this issue is rather limited.…”
Section: Catechol Content and Molecular Weightmentioning
confidence: 99%
“…[ 86 , 87 , 88 , 89 , 90 , 91 ] Mussel-inspired biomimetic polymers have been mainly prepared from polyesters, [88,89] polyamides, [ 92 ] polyacrylates, [ 93 , 94 , 95 , 96 ] polyethylene glycols, [16, 97 , 98 , 99 ] polyoxetanes, [87,91] polystyrenes [86,100 ] polypeptides [ 101 , 102 , 103 ] and polysaccharides. [104,105] The results defined a range of optimal catechol content close to that observed in mfps but with differences depending on the nature of the material used. However, despite this growing number of synthetic polymers mimicking mussel adhesive proteins, the number of detailed and systematic studies aimed at elucidating this issue is rather limited.…”
Section: Accepted Manuscriptmentioning
confidence: 70%